The Paradox of Religiosity–Secularism in Formal Religious Education - Meryem Karataş (Religions)
Creating a conceptual unity is an important starting point for understanding a subject. It is more difficult to find a common definition if the concept in question is ‘religion, religiosity, secularism’, which can vary according to the field of the person making the definition, where he/she positions himself/herself in relation to religion, the characteristics of the religion he/she believes in (or does not believe in), and many other parameters. In order to draw the boundaries of this research correctly, it is necessary to clarify the development and changes in the concept of ‘religion’ and the related concepts of ‘religiosity and secularism’ in the historical process. Among the places where the effectiveness of these concepts at the theoretical level can be examined are the textbooks taught in Anatolian Imam Hatip High Schools. The nature or content of the fiqh textbooks taught in Imam Hatip High Schools, which can be exemplified as an educational institution of religious culture reinforcement in Turkey, is within the scope of this study. In connection with this subject, the aim of this study is to analyse the fiqh and fiqh reading textbooks taught in Anatolian Imam Hatip High Schools from the perspective of religiosity and secularism. Fiqh, from the perspective of Islamic theology, contains normative principles that govern personal and social practices. As textbooks, fiqh and fiqh readings were chosen because they are likely to provide data on the subject. This research employs a qualitative approach, utilising document analysis as its primary method to investigate these textbooks. The analysis is based on textbooks that were approved by the Ministry of National Education and taught during the 2023–2024 academic year. For the purposes of this study, only explicit verbal content was considered, while implicit messages were excluded. As a result of this study, it is understood that both books have a religiosity-centred perspective and that there are chapters in which changes are taken into consideration rather than secularism.